1996
DOI: 10.1021/ac950998u
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mass Spectrometric Methods Applicable to the Direct Analysis of Non-Peptide Bead-Bound Combinatorial Libraries

Abstract: Electrospray, matrix-assisted laser desorption, and time-of-flight secondary ion mass spectrometry have been explored as possible methods for the identification of active members of molecular combinatorial libraries. All three methods are found to yield accurate molecular weight information about a target molecule angiotensin II antagonist synthesized on a 40-microns polystyrene bead. Structural identification is also possible by accurate mass measurements to eliminate candidate structures with the same nomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 23 publications
(28 reference statements)
0
52
0
Order By: Relevance
“…Maybe reactivity tests of building blocks with different forms of activation 26 can also be accelerated by such automated tests. Expanding the set of equireactive mixtures beyond amino acid building blocks 4 may revive the interest in mixed couplings as the simplest approach for generating diversity in untagged libraries, 27,28 including those that are so large as to require recursive deconvolution. 29 Some reactivities determined were quite unexpected and may, therefore, be of interest to the chemical community beyond the practical application of generating combinatorial libraries more efficiently.…”
Section: H) and Iodohippuric Acid (η) As Test Acid (T-co 2 H) (A)mentioning
confidence: 99%
“…Maybe reactivity tests of building blocks with different forms of activation 26 can also be accelerated by such automated tests. Expanding the set of equireactive mixtures beyond amino acid building blocks 4 may revive the interest in mixed couplings as the simplest approach for generating diversity in untagged libraries, 27,28 including those that are so large as to require recursive deconvolution. 29 Some reactivities determined were quite unexpected and may, therefore, be of interest to the chemical community beyond the practical application of generating combinatorial libraries more efficiently.…”
Section: H) and Iodohippuric Acid (η) As Test Acid (T-co 2 H) (A)mentioning
confidence: 99%
“…Such an edge effect was explained 12,33 as a consequence of superior conduction at the periphery of the bead leading to better charge neutralization. Finally, whereas the use of TFA vapors to cleave the covalent peptide-resin bond prior to imaging TOF-SIMS was found to provide some contamination as the ions were detected in part outside the beads, 18 well defined images were obtained in our case upon direct TOF-SIMS bombardment. The absence of physisorbed material was checked by selecting the protonated molecular ions of proline and phenylalanine at m/z 116 and 166, respectively, according to our previous study 32 (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…The structural information recovered from direct TOF-SIMS experiments was compared with the corresponding ESI and MALDI results obtained after compound release from the support. 18 Fitzgerald and co-workers 19,20 have described a method to analyze directly resin-bound peptides by MALDI mass spectrometry. The resin beads were derivatized by a photolabile linker which upon MALDI irradiation provided simultaneous peptide cleavage and ionization, thus not requiring chemical release in solution of the growing structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations